The Effect of Leadership Style and Mental Competency Guidance on Employee Performance with Work Engagement as a Mediating Variable at the Medium Customs Type, Customs and Excise Controlling and Servicing Office of Juanda - Janjang Subekti; Purwanto; Sri Rahayu (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2026)
This study aims to analyze the effect of leadership style and mental competency guidance on employee performance with work engagement as a mediating variable at the Medium Customs Type, Customs and Excise Controlling and Servicing Office of Juanda. This research employed a quantitative approach with an explanatory research design. The population consisted of all employees of the Medium Customs Type, Customs and Excise Controlling and Servicing Office of Juanda, totaling 208 employees. The sample size was determined using the Slovin formula with a 5% margin of error, resulting in 137 respondents. Data were collected through a questionnaire and analyzed using PLS-SEM. The results show that leadership style has a positive and significant effect on work engagement and employee performance. Mental competency guidance also has a positive and significant effect on work engagement and employee performance. Furthermore, work engagement has a positive and significant effect on employee performance. The mediation test confirms that work engagement mediates the effect of leadership style and mental competency guidance on employee performance. These findings indicate that improving employee performance can be achieved not only through leadership style and mental competency guidance directly, but also by strengthening employees’ work engagement. Therefore, the organization needs to enhance supportive leadership, practical mental competency guidance, and sustainable work engagement among employees.